Improved high altitude aerobic exercise performance following two weekly exercise bouts above 4000 meters - Chicco, A.; Turk, D.; DeMooy, A. B.; Andersen, B. (High Altitude Medicine & Biology, 2014)
We investigated whether single weekend bouts of aerobic exercise performed at high altitude separated by several days at lower altitude were sufficient to improve aerobic exercise capacity, arterial oxygen saturation (SaO2), hematocrit (HCT), and perceived exertion (RPE) during exercise at high altitude. Ten competitive runners (VO2max 53 - 2mL/kg/min, 41 - 5 years) naý¨ve to higher altitudes for at least 8 weeks prior to the study completed a timed 19km run on Mt. Evans (3500- 4300 m) followed by 1 week of routine training in Fort Collins (1524m). Runners were then randomized to perform either a 19km running workout at 1800-2100m (LOW, n = 4) or an identical workout at 4000-4300m (HIGH, n = 6). All runners then performed 1 week of routine training in Fort Collins before completing a post-training run identical to the baseline test performed 2 weeks earlier. The HIGH group experienced a 4.7 -2%improvement in high altitude run time (7.1 min faster; P = 0.09), while the LOW group ran 0.5 - 1.5% (1.3 min) slower (P =NS). Mean SaO2 was 3%higher in the HIGHin the post- vs. pre-test at 4300m (P = 0.02), but 1% lower in the LOW group. There were no differences in HCT or RPE between HIGHand LOWgroups. In conclusion, two consecutive weekend high altitude training bouts elicit a mild acclimatization response and improve subsequent high altitude aerobic exercise performance, while a single high altitude running bout separated by 2 weeks of low-altitude training is ineffective.